2014
DOI: 10.1002/ajmg.a.36697
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability associated with the invariant SHOC2 c.4A>G (p.Ser2Gly) missense mutation

Abstract: Noonan-like syndrome with loose anagen hair (NS/LAH; OMIM 607721) is a developmental disorder clinically related to Noonan syndrome (NS) and characterized by facial dysmorphisms, postnatal growth retardation, cardiac anomalies (in particular dysplasia of the mitral valve and septal defects), variable neurocognitive impairment, and florid ectodermal features. A distinctive trait of NS/LAH is its association with easily pluckable, slow growing, sparse, and thin hair. This rare condition is due to the invariant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
3
22
0
1
Order By: Relevance
“…Generalized hyperpigmentation was noted in 15%, almost always in adult patients, and it appeared highly specific to PTPN11 ‐NSML in our study as it was always absent in other NS genotypes. These results were consistent with previous studies, except for SOS1 ‐NS and SHOC2 ‐NS, for which hyperpigmentation was noted for an average of 49% and 68% of cases, respectively . Our strict definition of generalized hyperpigmentation excluded localized or partial forms of hyperpigmentation, and the inclusion of patients with an ethnic origin conferring a familial medium or dark skin colour could explain these results.…”
Section: Discussionsupporting
confidence: 92%
“…Generalized hyperpigmentation was noted in 15%, almost always in adult patients, and it appeared highly specific to PTPN11 ‐NSML in our study as it was always absent in other NS genotypes. These results were consistent with previous studies, except for SOS1 ‐NS and SHOC2 ‐NS, for which hyperpigmentation was noted for an average of 49% and 68% of cases, respectively . Our strict definition of generalized hyperpigmentation excluded localized or partial forms of hyperpigmentation, and the inclusion of patients with an ethnic origin conferring a familial medium or dark skin colour could explain these results.…”
Section: Discussionsupporting
confidence: 92%
“…One started GH treatment (Patient 1), but no growth data after treatment initiation were available at the time of this report. Ocular abnormalities occurred in three individuals reported here, these are common in patients with NS‐LAH [Baldassarre et al, ]. Relative or absolute macrocephaly with mildly enlarged ventricles and arachnoid spaces are seen in NS‐LAH [Gripp et al, ] and were present in all patients reported here.…”
Section: Discussionmentioning
confidence: 69%
“…These characteristics are suggestive of loose anagen hair, an abnormality resulting from abnormal root sheaths. Loose anagen hair is seen in most individuals with a recurrent point mutation in SHOC2 resulting in Noonan syndrome with loose anagen hair (NS‐LAH) [Cordeddu et al, ; Gripp et al, ; Baldassarre et al, ], in Costello syndrome due to the HRAS p.G13C mutation [Gripp et al, ] and rarely in cardio‐facio‐cutaneous syndrome [Wong Ramsey et al, ]. Short stature, often due to growth hormone deficiency, is common in NS‐LAH.…”
Section: Discussionmentioning
confidence: 99%
“…20,59 In following case reports on individuals with the SHOC2 p.S2G mutation, phenotypic variability was noted. 60 Costello syndrome is a rare RASopathy that is characterized by distinctive facial features, including full lips, a large mouth and a full nasal tip; soft skin with deep palmer and planter creases, failure to thrive, mild to severe intellectual disability and increased risk of malignant tumors are also characteristics of these patients. Germline activating mutations in HRAS (G12S in~80% of Costello syndrome patients) have been identified in individuals with Costello syndrome.…”
Section: Rasa1mentioning
confidence: 99%